A preparação para performance musical de quarteto de violões - Salgado, Rafael Pedrosa [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This work discusses strategies for the preparation of chamber music performance for guitar quartet. The main objective is determine how professionals Brazilian guitar quartets plan and conduct their trials. The methodology consisted of four main steps: 1) a review of the literature on preparation for musical performance in Portuguese and English, where was reviewed on individual performance as the chamber music performance; 2) developing and implementing a questionnaire to guitarists who work or have worked in professionals Brazilian guitar quartets; 3) a survey of the recorded repertoire audio and video by Brazilian quartet, illustrating the practice of transcription and arrangement for this formation and 4) suggestions of rehearsals procedures for guitar quartet, as learning facilitators and the rapport between the musicians in this chamber formation. The main conclusion determines the strategies used by Brazilian guitar quartets in preparing their musical performances and suggests strategies targeted to the specific characteristics of training as means of optimization of that preparation

Este trabalho discute estratégias para a preparação da performance de música de câmara para quarteto de violões. O principal objetivo é determinar como quartetos de violões brasileiros profissionais planejam e realizam seus ensaios. A metodologia consistiu em quatro etapas principais: 1) uma revisão da literatura sobre preparação para performance musical em língua portuguesa e inglesa, onde se verificou tanto trabalhos sobre performance individual quanto da performance da música de câmara; 2) elaboração e aplicação de um questionário a violonistas que atuam ou atuaram em quartetos brasileiros profissionais de violões; 3) um levantamento do repertório gravado em áudio e vídeo por quartetos brasileiros, ilustrando a prática da transcrição e arranjo para esta formação e 4) elaboração de sugestões de procedimentos de ensaio para quarteto de violões, como facilitadores da aprendizagem e do entrosamento entre os instrumentistas na formação de câmara. A principal conclusão determina as estratégias mias utilizadas por quartetos de violões brasileiros na preparação de suas performances musicais e sugere estratégias direcionadas para as especificidades desta formação como formas de otimização da referida preparação
Keywords: Música - Execução; Violão - Instrução e estudo; Música para violão; Quartetos de cordas; Música de câmara; Music Performance